Balloon Angioplasty Versus Stenting for the Treatment of Failing Arteriovenous Grafts: A Meta-Analysis. (February 2018) - Kouvelos, George N.; Spanos, Konstantinos; Antoniou, George A.; Vassilopoulos, Ioannis; Karathanos, Christos; Matsagkas, Miltiadis I.; Giannoukas, Athanasios D.
Abstract : Purpose: To assess the outcomes of plain balloon angioplasty versus stenting for the treatment of failed or malfunctioning chronic haemodialysis arteriovenous grafts (AVGs). Methods: A systematic search of the literature was undertaken using the PUBMED, EMBASE, and Cochrane databases from January 2000 to September 2016 for articles comparing balloon angioplasty versus stenting in the management of failed or malfunctioning chronic haemodialysis AVGs. Results are reported as OR and 95% CI. Results: The search identified eight studies (1051 patients). Balloon angioplasty alone was used in 521 patients (49.6%) and stenting in 530 patients (50.4%). At the time of the endovascular re-intervention, the mean life of AVGs was 807.7±115.4 days for the balloon angioplasty and 714.2±96.3 days for the stenting group ( p =.92). All AVGs were located in the arm. Most procedures (98.1%) were performed across the venous anastomosis, while 88% of the patients in the stenting group received a stent graft. The technical success rate was significantly higher in the stenting group (OR 0.16, 95% CI 0.08–0.31, p <.001). At 12 months, loss of primary and secondary patency was significantly higher in patients undergoing plain balloon angioplasty compared with stenting (OR 3.54, 95% CI 2.18–5.74, p <.001, and OR 1.82, 95% 1.17–2.82, p =.008, respectively). Conclusion: Stenting is associated with better technical success and patency rates compared with plain angioplasty in treating failed or malfunctioning chronic haemodialysis AVGs, and thus it should be considered as the first line therapeutic option.